PENERAPAN AUGMENTED REALITY UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Dhimas Mahendra; Desty Endrawati Subroto; Barokah Barokah; Evi Mudoifah; Diah Mudafiah (CV. Denasya Smart Publisher, 2025)
Augmented Reality (AR) technology has made significant progress since it was first introduced by Thomas P. Caudell in 1992 as an industrial support tool. Today, the application of AR has become increasingly widespread, including in the field of education. This study aims to evaluate the effectiveness of Augmented Reality as a 3D-based learning medium to enhance student motivation for learning. The research was conducted with 32 third-grade students at SDN 1 Daroyon using a qualitative-descriptive research approach. Through a discovery learning approach, students were introduced to abstract concepts with the help of AR, which allows real-time visualization of virtual objects. The results of the study show that before using AR, 58% of students had very low learning motivation. However, after the implementation of AR, there was a significant increase in motivation, with 65% of students showing very high learning motivation. In addition to increasing interest and motivation, the use of AR also enriches students' learning experiences through interactive 3D visual features. This technology helps students understand abstract concepts in a more engaging and efficient way compared to traditional learning methods. The conclusion of this study emphasizes that integrating AR into the learning process can be an innovative approach to improving the quality of education. Specifically, this technology is effective in enhancing student motivation toward the subject matter. These findings support the importance of adopting modern technology in education to create a more dynamic and relevant learning environment in today's digital era.